Holistic-Integrative Early Childhood Education and Its Impact on Social-Emotional, Physical, and Cognitive Development: A Multi-Regional Regression Analysis - Gea, Jeni Juniarwati; Diana, Diana; Aeni, Kurotul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
There is a notable gap in the literature regarding the implementation of Holistic-Integrative Early Childhood Development (PAUD HI) in Indonesia, particularly within PAUD institutions under the PESAT Foundation, which operates across multiple regions. Few studies have specifically examined the impact of PAUD HI on core dimensions of early childhood development—social-emotional, physical-motor, and cognitive—which are foundational pillars in early childhood education. This study investigates the influence of PAUD HI implementation on children's social-emotional, physical-motor, and cognitive development in PESAT Foundation-affiliated institutions. A total of 122 early childhood education teachers were selected as respondents through an online survey using Google Forms. Collected data were analyzed using SPSS version 24, employing descriptive statistics, normality tests, significance tests, regression analysis, and hypothesis testing to examine the relationships between PAUD HI practices and child development outcomes. Findings demonstrate a significant positive impact of PAUD HI on social-emotional and physical-motor development, with contributions exceeding 80%. The presence of a supportive, interactive, and cross-sectorally collaborative learning environment enriches children’s learning experiences. While the influence on cognitive development is also positive, it is relatively lower, highlighting the need for more targeted and contextualized instructional strategies. This study underscores the importance of a multidisciplinary approach in PAUD HI to support children’s comprehensive development. However, the quantitative design limits in-depth exploration of the contextual dynamics of PAUD HI implementation. The absence of qualitative data restricts understanding of social interactions, local challenges, and emerging best practices. Future research is recommended to adopt qualitative or mixed-methods approaches to generate more comprehensive insights into the effectiveness and challenges of PAUD HI across diverse regional contexts.